Effect of environmental education program integrated into preschool education on children’s mental model development about “environment” concept - Ahi, Berat; Alisinanoglu, Fatma (Birlesik Dunya Yenilik Arastirma ve Yayincilik Merkezi, 2018)
Aim of this study is to determine the effect of environmental education program integrated into preschool education aged between 48-66 months on children’s mental model development about “environment” concept. Triangular mixed design was used in this research. Quantitative dimension of the study was carried out with quasi-experimental design with control group and qualitative dimension of the study was carried out with using phenomenological method based on social constructivist philosophy. Study group of the research consisted of 52 children from experimental and control groups. Statistically significant difference was observed in the scores of children in the experimental and control groups from DAET-R (U= 44, z= -5.44, p= .000, r= .75). Mental model development about environment of the majority of the children from the experimental group reached to an expected level. However, no development was obtained in the mental model development of the children in the control group. Results also showed that 80.8% of the children from experimental group defined environment as a place which people, animals and plants live together and the amount of the children from control group who defined environment similar to this level is 26.9%. In addition, there was no significant difference in the total pre-test and post-test DAET-R scores of children from the control group (z= -1.401, p > .05) and significant difference was observed in the pre-test and post-test DAET-R scores of children in the experimental group in support of post-test results (z= -4.126, p < .05). Keywords: Environment; Mental Model; Child; Pre-school Educatio; Environmental Education
Keywords: 13. Climate action; 4. Education; 3. Good health